Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1987
DOI: 10.1111/j.1432-1033.1987.tb10552.x
|View full text |Cite
|
Sign up to set email alerts
|

Further biochemical characterization of an Na+ pump inhibitor purified from human urine

Abstract: An increase in endogenous Na+,K+‐ATPase inhibitor(s) with digitalis‐like properties has been reported in chronic renal insufficiency, in Na+‐dependent experimental hypertension and in some essential hypertensive patients. The present study specifies some properties and some biochemical characteristics of a semipurified compound from human urine having digitalis‐like properties. The urine‐derived inhibitor (endalin) inhibits Na+,K+‐ATPase activity and [3H]‐ouabain binding, and cross‐reacts with antidigoxin anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1988
1988
1996
1996

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…From these studies, digoxin (9) and "iso-ouabain" (10-13) have been isolated; however, digoxin and ouabain lead to kaliuresis (4,(14)(15)(16)(17). Therefore, we hypothesized that this search tool is an inadequate marker for natriuresis.…”
Section: Introductionmentioning
confidence: 99%
“…From these studies, digoxin (9) and "iso-ouabain" (10-13) have been isolated; however, digoxin and ouabain lead to kaliuresis (4,(14)(15)(16)(17). Therefore, we hypothesized that this search tool is an inadequate marker for natriuresis.…”
Section: Introductionmentioning
confidence: 99%
“…Kramer et al (30), studying a semi-purified urinary inhibitor, described the NH inhibition of Na-K-ATPase as noncompetitive with respect to potassium. Crabos et al (31) reported that NH, also isolated from urine, inhibited Na-K-ATPase noncompetitively with respect to ATP. Inhibition of the enzyme system was facilitated by sodium.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of the enzyme system was facilitated by sodium. Ouabain, a digitalis glycoside and a specific inhibitor of the Na-K-ATPase system, has been shown to be competitive with respect to potassium (32) and noncompetitive with respect to ATP (31). In the present study, we employed a semi-purified NH preparation derived from plasma of a patient with essential hypertension to perform kinetic studies.…”
Section: Discussionmentioning
confidence: 99%
“…Kramer et al (30), studying a semi-purified urinary inhibitor, described the NH inhibition of Na-K-ATPase as noncompetitive with respect to potassium. Crabos et al (31) reported that NH, also isolated from urine, inhibited Na-K-ATPase noncompetitively with respect to ATP. Inhibition of the enzyme system was facilitated by sodium.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of the enzyme system was facilitated by sodium. Ouabain, a digitalis glycoside and a specific inhibitor of the Na-K-ATPase system, has been shown to be competitive with respect to potassium (32) and noncompetitive with respect to ATP (31). In the present study, we employed a semi-purified NH preparation derived from plasma of a patient with essential hypertension to perform kinetic studies.…”
Section: Discussionmentioning
confidence: 99%